2013
DOI: 10.13102/sociobiology.v60i4.477-483
|View full text |Cite
|
Sign up to set email alerts
|

Phenology of European Hornet, Vespa crabro L. and Saxon Wasps, Dolichovespula saxonica Fabr. (Hymenoptera: Vespidae) and the Influence of the Weather on the Reproductive Success of Wasps Societies in Urban Conditions

Abstract: In subsequent years, changes in the period of colonies activity for both species of wasps were observed as well as the longer period of development of wasp societies in the city than in the forest. There was not found a clear influence of weather conditions in winter on date of colonies initiation. However, low temperatures and rainfall in May caused delaying the initiation of nesting. The temperature in winter had a little impact on the number of queens that survived the winter and established their colonies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 12 publications
1
6
0
Order By: Relevance
“…This is an evidence of a high colony cycle synchrony degree, as described for some independent-founding wasps (Dantas de Araujo, 1982). However, since 61.5% of the species were also present in the winter, our results agree with Naldoski (2013), who suggests that the complexity of urban environments reduces the impact of seasons on the social wasp cycles.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…This is an evidence of a high colony cycle synchrony degree, as described for some independent-founding wasps (Dantas de Araujo, 1982). However, since 61.5% of the species were also present in the winter, our results agree with Naldoski (2013), who suggests that the complexity of urban environments reduces the impact of seasons on the social wasp cycles.…”
Section: Resultssupporting
confidence: 92%
“…Alvarenga et al, 2010;Jacques et al, 2012;Naldoski, 2013;Torres et al, 2014;see Barbosa et al, 2016). They show the relation between many species of social wasps and their environments, such as how some species found in urban areas depend exclusively on natural vegetation, whereas other prefer artificial substrates (Alvarenga et al, 2010;Sinzato et al, 2011;Castro et al, 2014;Virgínio et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…abundance (see also Nadolski 2013, Lester et al 2017. Second, we did not measure wasp abundance for each nest separately, but in two large areas in central and northern Netherlands.…”
Section: Discussionmentioning
confidence: 99%
“…Whilst this represents a substantial resource for species such as Blue Tits and Great Tits, it also offers nesting opportunities in favourable habitat for Tree Bumblebees, Saxon Wasps and Hornets, and this may be unwelcome by some homeowners concerned with stinging insects breeding close to their home (Nadolski 2013). However, Lye et al (2012) found that only 10% of bumblebee nests reported from English gardens were in nest-boxes, and Kozłowski (1992) found only 'sporadic' breeding by wasps (and no bumblebees) in nest-boxes in Warsaw's (Poland) urban parks.…”
Section: Discussionmentioning
confidence: 99%
“…Hornets are considered to prefer woodland habitats in Britain (Phillips & Roberts 2010a), where they may occupy nest-boxes intended for passerines (Holmes 2009). Hornet nests, however, are frequent in suburban areas in other parts of Europe (Langowska et al 2010, Nadolski 2013 and tree planting could be aiding its expansion into British gardens (Phillips & Roberts 2010a). Therefore, while the expansion of the Hornet's range and colonization of Britain by the Tree Bumblebee and Saxon Wasp may have increased nestsite competition for cavity-nesting birds, quantitative information is lacking.…”
mentioning
confidence: 99%